The effects of video game trounament play on the level of morale of geriatric residents in a nursing home setting - Olson, Lorene S. (My University, 1985)
A Pac-Man tournament was implemented to evaluate the effects of video game tournament play on the levels of morale of geriatric residents at Bethany-St. Joseph Care Center. 40 Ss were randomly assigned to one of two groups. The experimental group (N=20) participated in the video game tournament play which consisted of daily pac-man play on 19 consecutive weekdays. The remaining 20 Ss comprised the control group and did not participate in-the tournament play. Pre and post experiment morale levels of all Ss were measured by the Philadelphia Geriatric Center-(PGC) Morale Scale. Chi square analysis of the total P scores from the PGC Morale Scale, indicating overall level of morale, indicated a significant difference (p <.05) between the two groups. The statistical findings in this study documented the effectiveness of video game tournament play in improving the morale of geriatric residents in a nursing home setting.
Keywords: Care.; Nursing home patients.; Psychological aspects.; Video games.